Financial Support of Entrepreneurship in Countries of EEU - Vasiliy A. Sviridovich (Евразийская интеграция: экономика, право, политика, 2019)
Purpose of the article is the analyze of financial support of small and medium businesses, which is implemented in all states of Eurasian Economic Union. Author researched the role of crediting and insurance, which have a big potential to here. In this researching was used official statistical information, informative and structural analysis, which allow to ensure to logicality and consistency for that work. In result author detected regularities and problems, which have all states of Eurasian Economic Union in common. This is evidence a financial support, which small and medium businesses get every year, is not enough sufficient and stable. This leads to objective constriction production and economic activity of self-employed and stagnation of this economic sector of Eurasian Economic Union.